MEDIA SURVEILLIANCE AND PRESSURE OF INTELLIGENCE AND PARAMILITARY GROUPS: THE CASE OF IRAN - Görgülü, Yusuf (Mehmet Akif KARA, 2020)
The need for information has increased in direct promotion to development of communication Technologies in today’s world, Intellıgence Organizations ara in an efford to gain a strong place both inside and outside the country. The success of an intelligence agency can be achieved primarily by creating a strong information network within the country so that it can prepare a ground suitable for external espionage movements. Those in power want to be informed about the individuals living in the country. Therefore, it is in contact with the Intelligence units and some paramilitary groups in the country, and sometimes the public power draws Intelligence organizations into its dynamic center. With the legitimate power of this paramilitary and intelligence agency in the public sphere, the creation of a domination field over the others will lead to the emergence of a monophonic dynamic structure in the country, the development of valuable conflicts in the transformations in social formations and the loss of awareness concerning to being a society.The research was limited to the activities of Iranian Intelligence Mois and other paramilitary groups, and the literature review method was used in the research. The aim of this study is to reveal the attitude of Iranian Intelligence and other paramilitary groups towards the media along with the development process. In our study, it was concluded that intelligence and paramilitaries started to create all kinds of domination for the press and other media groups in order to create a single ideological and valuable environment in the country, and many reformist newspapers and magazines were closed and they were exposed to censorship.

Günümüz dünyasında iletişim teknolojilerinin gelişmesi ile birlikte bilgiye olan ihtiyaçta doğru orantılı olarak artmıştır. Günümüzde İstihbarat örgütleri hem ülke içerisinde hem de ülke dışında güçlü bir yer edinme çabası içerisindedir. Bir İstihbarat örgütünün başarısı öncelikle ülke içerisinde güçlü bir bilgi ağının oluşturulması ile sağlanabilir ki dış espiyonaj hareketlerine uygun bir zemin hazırlayabilsin. İktidarı elinde bulunduranlar ülke içerisinde yaşayan bireyler hakkında haberdar olmak istemektedirler. Bu yüzden ülke içerisinde yer alan İstihbarat birimleri ve bazı paramiliter gruplar ile temas halinde bulunmakta ve bazen kamusal güç, İstihbarat örgütlerini kendi dinamik merkezi içerisine de çekmektedir. Bu paramiliter ve istihbarat örgütünün kamusal alandaki mevcut meşru gücü ile ötekiler üzerinde bir tahakküm alanının yaratılması ülkede tek sesli dinamik bir yapının ortaya çıkmasına, toplumsal formasyonlardaki dönüşümlerdeki değersel çatışmaların gelişimini ve toplum olma bilincinin kaybolmasına sebebiyet verecektir.Araştırma İran İstihbaratı Mois’in faaliyetleri ve diğer paramiliter gruplar ile sınırlandırılmış olup, araştırmada literatür taraması yöntemi kullanılmıştır. Bu çalışmanın amacı, İran İstihbaratı ve diğer paramiliter grupların gelişim süreci ile birlikte medyaya yönelik tutumlarını ortaya çıkarmaktır. Araştırmamızda İstihbarat ve paramiliter grupların ülkede tek bir ideolojik ve değersel ortam oluşturma güdüsünde basın ve diğer medya gruplarına yönelik her türlü tahakküm alanı yaratma amacı içerisinde giriştiği, pek çok reformist gazete ve dergilerin kapatıldığı ve sansüre maruz kaldıkları sonucuna ulaşılmıştır.
İSTİHBARAT VE PARAMİLİTER GRUPLARIN MEDYAYA YÖNELİK GÖZETİMİ VE BASKISI: İRAN ÖRNEĞİ